MUSCULOSKELETAL DISORDERS AND ERGONOMIC RISKS IN A FLORICULTURAL COMPANY, MACHACHI, 2023 - Maritza Leidy Yánez Morillo; Cristina E. Almeida-Naranjo; Juan Carlos Flores; Navarrete Alboreda Edmundo Daniel (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study explored the relationship between ergonomic risks and the development of musculoskeletal disorders (MSDs) among post-harvest personnel at a floriculture company in Machachi during 2023. Using a quantitative approach, two main instruments were employed: the Nordic questionnaire and the RULA method. The research revealed a significant correlation between MSDs and ergonomic risks in the workplace, with a correlation coefficient of 0,457, indicating a meaningful relationship between these variables.It was observed that bunchers experienced a high incidence of musculoskeletal issues in both arms and forearms, each at 87,5%. Similarly, cutters showed uniform impacts in the same regions. Classifiers reported a high prevalence of neck disorders at 76.9%. Age group analysis revealed that younger workers, aged 20 to 25, primarily experienced leg disorders, represented by 33.3%. In contrast, the 36 to 45 age group showed a very low prevalence of musculoskeletal discomfort, with the neck being the most affected area at only 10.7%. Workers aged 40 to 60 had the highest incidence of leg problems, represented by 33.3%.In terms of gender, it was found that women experienced musculoskeletal discomfort in the right arm, forearm, and wrist at 57,7%, compared to men who reported 42,3%. Finally, the RULA method assessment identified that the positions of buncher, cutter, and classifier, with a score of 6, require immediate action and task redesign due to a high level of ergonomic risk. In contrast, the packer position scored four, indicating that task changes are needed to mitigate risks.